ANALISIS YURIDIS DISKRESI KEPOLISIAN DALAM PENERAPAN DIVERSI - I KETUT SEREGIG (PRANATA HUKUM, 2017)
The problem of diversion is often used as a legal reason for the parties involved as a suspect in a crime committed by a minor, both for the purpose of defense and in an attempt to avoid a suspect from imprisonment stipulated in the provisions of the law. Diversi as stipulated in Article 1 point 7 of Law Number 11 Year 2012, on the Criminal Justice System of the Child, is the transfer of the settlement of child cases from the criminal justice process to proceedings outside the criminal justice.In the case of the transfer of cases of perpetrators of minor offenses, there have been various perceptions or differences of legal views, especially the understanding of "repetition of criminal acts". In criminal law theory the term repetition of a criminal offense is the same offense committed by a person more than once. In social life in society the perpetrator is called a residivist. In the process of investigating the application of the versions of underage residivists is a legal policy undertaken by the investigator in assessing whether the perpetrator deserves a diversion or not.The result of the research can be concluded that the implementation of the diversion for underage perpetrators who perform repetition of acts in legal theory and legislation can be done as a form of police discretion conducted by investigators. The discretion made by the investigator is done on the coordination of Police investigators with other agencies, especially the Court, BAPAS, the victim's parents and the Legal Counsel accompanying the victim and other related parties. The problem of diversion is often used as a legal reason for the parties involved as a suspect in a crime committed by a minor, both for the purpose of defense and in an attempt to avoid a suspect from imprisonment stipulated in the provisions of the law. Diversi as stipulated in Article 1 point 7 of Law Number 11 Year 2012, on the Criminal Justice System of the Child, is the transfer of the settlement of child cases from the criminal justice process to proceedings outside the criminal justice.In the case of the transfer of cases of perpetrators of minor offenses, there have been various perceptions or differences of legal views, especially the understanding of "repetition of criminal acts". In criminal law theory the term repetition of a criminal offense is the same offense committed by a person more than once. In social life in society the perpetrator is called a residivist. In the process of investigating the application of the versions of underage residivists is a legal policy undertaken by the investigator in assessing whether the perpetrator deserves a diversion or not.The result of the research can be concluded that the implementation of the diversion for underage perpetrators who perform repetition of acts in legal theory and legislation can be done as a form of police discretion conducted by investigators. The discretion made by the investigator is done on the coordination of Police investigators with other agencies, especially the Court, BAPAS, the victim's parents and the Legal Counsel accompanying the victim and other related parties.